Helicobacter pylori Infection in Patients with Portal Hypertensive Gastropathy Owing to Liver Cirrhosis: Prevalence and Relation with Severity of Gastropathy - Puri, Shekhar; Jain, Mukesh; Narayan, Kumar Shwetanshu; Pandey, Sudhakar; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2017)
Background and Aim: Helicobacter pylori is a major human pathogen. Its role in the pathogenesis of portal hypertensive gastropathy (PHG) is debated. The aim of this study was to evaluate the prevalence of this infection in patients with portal hypertension due to liver cirrhosis and its relation with severity of gastropathy. Patients and Methods: Sixty consecutive patients with liver cirrhosis were enrolled in the study. All patients were subjected to an upper gastrointestinal endoscopy (UGIE), and rapid urease testing for H. pylori was performed. The diagnosis and severity of PHG was evaluated on UGIE. ChildαTurcotteαPugh (CTP) and model for endαstage liver disease (MELD) scores were calculated to assess the severity of liver cirrhosis. Results:H. pylori infection was reported in 33 patients with overall prevalence 55%. The presence of H. pylori was observed in 26 (67%) cirrhotic patients with PHG compared to 7 (33%) cirrhotic patients without PHG. The risk estimate showed a significant association between H. pylori and PHG in cirrhotic patients (P = 0.0133, odds ratio [OR]: 4.00, 95% confidence interval [CI]: 1.298–12.325). Out of the 26 patients with PHG and H. pylori infection, 17 had severe PHG (65.3%) and 9 had mild PHG (34.6%) whereas 4 patients had severe PHG (30.8%) and 9 had mild PHG (69.2%%) in the group of H. pyloriαnegative patients. The difference was statistically significant (P = 0.04, OR: 4.25, 95% CI: 1.0188–17.729). Of the 39 patients with PHG, 21 (53.85%) had severe PHG and 18 (46.15%) had mild PHG. No significant relation was found between H. pylori infection and severity of liver cirrhosis as regards CTP score (P = 0.76) and MELD score (P = 0.56). Conclusion: Our results showed a significant association between H. pylori infection and the occurrence and also the severity of gastropathy in patients with liver cirrhosis. Yet, the severity of liver cirrhosis itself did not correlate with H. pylori or the severity of gastropathy.
Keywords: Helicobacter pylori; liver cirrhosis; portal hypertensive gastropathy